Critical Language Pedagogy and Task-Based Language Teaching: Reciprocal Relationship and Mutual Benefit - Graham V. Crookes; Nicole Ziegler (MDPI AG, 2021)
Curriculum development and empirical research in the field of second language acquisition could benefit the field of critical language pedagogy (CLP) and its practitioners. This article reviews central concepts in the organization of curriculum in CLP and compares them with another major curricular initiative in second language teaching, namely task-based or task-supported approaches, with particular emphasis on task-based language teaching. Content itself (as in activities or materials) and the role of metacognitive instruction are considered. A real-world example of a task-based or task-supported short-term program is reviewed as exemplifying some areas of contact or benefit.